A Systematic Review of Surgical Techniques for Management of Severe Rhinophyma. Issue 4 (December 2021) - Benyo, Sarah; Saadi, Robert A.; Walen, Scott; Lighthall, Jessyka G.
Study Design: Systematic review of the literature. Objective: The goal of this study is to review the current literature on severe rhinophyma requiring operative management for significant cosmetic deformity or nasal obstruction. We aim to provide a treatment algorithm for the various surgical techniques employed in the treatment of severe rhinophyma. Methods: Independent searches of the PubMed and MEDLINE databases were performed. Articles from the period of 2010 to 2020 were collected. All studies which described surgical treatment of severe rhinophyma using the Boolean method and relevant search term combinations, including "rhinophyma, " "severe, " "operative" and "surgery" were collected. Results: A total of 111 relevant unique articles met criteria for eligibility analysis. Of these, 85 articles were deemed inappropriate for the literature review due to exclusion criteria. The remaining 26 articles were included in the literature review. Due to variability in study design and outcome measures, formal synthesis of data in the form of a meta-analysis was not possible. Conclusions: Severe rhinophyma may present a reconstructive challenge to reestablish normal contour and patent nasal airway. Significant deformity necessitates surgical correction. The present article reviews the current literature and provides a summary and stepwise explanation of established surgical techniques for addressing the cosmetic and functional deficits these patients encounter.